Desenvolvimento de uma unidade de ensino potencialmente significativa usando metodologias ativas para o ensino de forças nucleares - Souza, Edson Elias de (2019)
The present work exposes an investigation that searchs to analyze the contributions for Nuclear Physics teaching in high school, from the utilization of a methodological approach supported on the premises of meaningful learning (ML) developed by the psych